The Influence of Genetic Variants on Striatal Dopamine Transporter and D2 Receptor Binding after TB. Issue 8 (August 2014) - Wagner, Amy K; Scanion, Joelle M; Becker, Carl R; Ritter, Anne C; Niyonkuru, Christian; Dixon, Clifton E; Conley, Yvette P; Price, Julie C
Dopamine (DA) neurotransmission influences cognition and recovery after traumatic brain injury (TBI). We explored whether functional genetic variants affecting the DA transporter (DAT) and D2 receptor (DRD2) impacted in vivo dopaminergic binding with positron emission tomography (PET) using [ 11 C]βCFT and [ 11 C]raclopride. We examined subjects with moderate/severe TBI ( N = 12) 1 year post injury and similarly matched healthy controls ( N = 13). The variable number of tandem repeat polymorphism within the DAT gene and the Taql restriction fragment length polymorphism near the DRD2 gene were assessed. TBI subjects had age-adjusted DAT-binding reductions in the caudate, putamen, and ventral striatum, and modestly increased D2 binding in ventral striatum versus controls. Despite small sample sizes, multivariate analysis showed lower caudate and putamen DAT binding among DAT 9-allele carriers and DRD2 A2/A2 homozygotes with TBI versus controls with the same genotype. Among TBI subjects, 9-allele carriers had lower caudate and putamen binding than 10/10 homozygotes. This PET study suggests a hypodopaminergic environment and altered DRD2 autoreceptor DAT interactions that may influence DA transmission after TBI. Future work will relate these findings to cognitive performance; future studies are required to determine how DRD2/DAT1 genotype and DA-ligand binding are associated with neurostimulant response and TBI recovery.